DETERMINING THE RELATION BETWEEN PERSONALITY TRAITS AND LIFE SATISFACTION LEVELS OF BODY BUILDING TRAINERS - GEÇER, Alen; TAZEGÜL, Ünsal (IJRDO- Journal of Educational Research, 2016)
The aim of this research was to determine the relation between personality traits and life satisfactionlevels of body building trainers. Sample of the study consisted of 76 body building trainers whovolunteered in the study. Life Satisfaction Scale and Reviewed Eysenck Personality QuestionnaireAbbreviatedForm were used as data collection means. SPSS 20 package program was used in dataanalysis. “Kolmogorov-Smirnov” test was used so as to determine that data have normal distributionand “Anova-Homogeneity of Variances” test was applied to determine homogeneity of the data and itwas determined that data are homogeneous and have a normal distribution. After this first review, useof parametric test method was decided for statistical analysis of the data. Descriptive statistics andPearson correlation and Regression analysis were used in data analysis. As a result of the study, it wasfound that body building trainers have high score in extroversion and that there is a negative waymedium level relation between life satisfaction score and neuroticism and psychoticism dimensions ofbody building trainers.Key Words: Body building, personality, life satisfaction.